2021
DOI: 10.3389/fphar.2020.569466
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Fatal Multiorgan Failure and Heterochronous Pneumonitis Following Pembrolizumab Treatment in a Patient With Large-Cell Neuroendocrine Carcinoma of Lung

Abstract: Immune checkpoint inhibitors have radically changed the landscape of antitumor therapies in several malignancies. Despite the long-term efficacy, severe immune-related adverse events (irAEs) were not uncommon. However, fatal simultaneous multiorgan failure was rare. Here, we described a patient who developed multiorgan failure, including fulminant myocarditis, myasthenia gravis crisis, hepatic dysfunction, and delayed pneumonitis after pembrolizumab therapy for lung large-cell neuroendocrine carcinoma. After f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We searched PubMed for relevant articles to validate our findings and selected 30 patients for analysis ( Katsume et al, 2018 ; Khoury et al, 2019 ; Wang and Hu, 2019 ; Balanescu et al, 2020 ; Diamantopoulos et al, 2020 ; Hardy et al, 2020 ; Hyun et al, 2020 ; Leaver et al, 2020 ; Szuchan et al, 2020 ; Tu et al, 2020 ; Valenti-Azcarate et al, 2020 ; Wang et al, 2020 ; Xie et al, 2020 ; Xing et al, 2020 ; Arangalage et al, 2021 ; Cham et al, 2021 ; Chen et al, 2021 ; Elder et al, 2021 ; Iwasaki et al, 2021 ; Komatsu et al, 2021 ; Liang et al, 2021 ; Tanabe et al, 2021 ; Yanase et al, 2021 ; Zhang et al, 2021 ). The results are coincident with ours.…”
Section: Resultsmentioning
confidence: 96%
“…We searched PubMed for relevant articles to validate our findings and selected 30 patients for analysis ( Katsume et al, 2018 ; Khoury et al, 2019 ; Wang and Hu, 2019 ; Balanescu et al, 2020 ; Diamantopoulos et al, 2020 ; Hardy et al, 2020 ; Hyun et al, 2020 ; Leaver et al, 2020 ; Szuchan et al, 2020 ; Tu et al, 2020 ; Valenti-Azcarate et al, 2020 ; Wang et al, 2020 ; Xie et al, 2020 ; Xing et al, 2020 ; Arangalage et al, 2021 ; Cham et al, 2021 ; Chen et al, 2021 ; Elder et al, 2021 ; Iwasaki et al, 2021 ; Komatsu et al, 2021 ; Liang et al, 2021 ; Tanabe et al, 2021 ; Yanase et al, 2021 ; Zhang et al, 2021 ). The results are coincident with ours.…”
Section: Resultsmentioning
confidence: 96%
“…He recovered from the acute phase of MOF, but he subsequently developed a delayed immune-related pneumonia (about 8 weeks after the end of the immunotherapy treatment), responsive to treatment with methylprednisolone. [15] A retrospective study by Salem et al in 2018 reported the association between ICI treatment and the onset of myocarditis: this AE had a median onset time of 30 days from the start of immunotherapy and in 64% of cases it occurred between the first and the second course of treatment. [16] Moreover, a multicentric study by Mahmood et al showed a 1.14% prevalence of myocarditis in patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…After that, duplicated descriptions of clinical cases that were found in different articles from the same institution were excluded. In the end, 160 articles describing 244 cases were selected [ 16 , 29 , 31 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , …”
Section: Methodsmentioning
confidence: 99%